On dirty hands and definitions: a rejoinder - Mastrofski, Stephen D. (Journal of research in crime and delinquency, 1993)
The authors comment on criticisms regarding their review of the books Policing Domestic Violence, by Lawrence W. Sherman, and Above the Law. In their opinion, researchers often face moral dilemmas when they wish to make policy recommendations from their studies and that regrettable choices will be made. However, they claim that Sherman has not outlined an argument that justifies the recommendations he has made. They cite the problem with the definition of excessive force in Above the Law